A local assessment toolkit to promote deeper learning: transforming research into practice - Hess, Karin (Corwin, 2018)
Watch your system become greater than its parts by building local capacity through common language and deeper knowledge of assessment components. For years, educators have turned to the Hess Cognitive Rigor Matrices (CRM). Now for the first time, the modules are packaged into one resource to help you evaluate the quality and premise of your current assessment system. Designed as a professional development guide for long-term use by school leaders, five content-rich, topic-based modules: